2014
DOI: 10.1021/mz5000152
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Concentration and Segmental Flow Alignment in a Shear-Banding Solution of Polymer-Like Micelles

Abstract: We measure the spatially resolved microstructure and concentration in the plane of flow for a viscoelastic solution of polymer-like micelles comprised of mass fraction 6.0% (volume fraction 6.6%) solution of 2:1 molar ratio cetylpyridinium chloride/sodium salicylate in 0.5 mol/L NaCl/D2O through the shear banding transition. Spatially resolved flow small-angle neutron scattering measurements in the velocity–velocity gradient (1–2) plane of flow establish the local microstructure, and scanning narrow-aperture f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…In Fig. 6 Recent scanning narrow-aperture flow ultrasmall-angle neutron scattering experiments have demonstrated that the formation of shear bands is connected to the strong alignment of micelles at the rotating wall, where they align along the flow direction and form a high shear rate band, whereas the remaining region is composed of less ordered micelles, constituting the lower shear rate band [10,26,46]. This is exemplified by butterflylike patterns as observed earlier by Refs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In Fig. 6 Recent scanning narrow-aperture flow ultrasmall-angle neutron scattering experiments have demonstrated that the formation of shear bands is connected to the strong alignment of micelles at the rotating wall, where they align along the flow direction and form a high shear rate band, whereas the remaining region is composed of less ordered micelles, constituting the lower shear rate band [10,26,46]. This is exemplified by butterflylike patterns as observed earlier by Refs.…”
Section: Discussionsupporting
confidence: 56%
“…Macroscopically, this phenomenon consists in a transition from a homogeneous to an inhomogeneous state characterized by a shear rate independence of the shear stress on * danila.gaudino@unina.it the macroscopic shear rate [22,23]. Microscopically, shear banding is related to the coexistence of a paranematic band and a quasi-isotropic one, where micelles are aligned along the flow direction and entangled as in the quasi-quiescent state, respectively [19,[24][25][26]. It must be stressed that, although shear banding has been widely observed, a definitive physical explanation, in particular of the microscopic mechanisms leading to shear banding development, is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…This is shown for long, linear, entangled WLMs in Fig. 2, [25]. However, as the angular frequency approaches the inverse of the breaking time of the micelles, deviations from this simplistic behavior are observed.…”
Section: Linear Viscoelasticitymentioning
confidence: 79%
“…Cole-Cole plot for a highly entangled solution of linear micelles of CPCL/NaSal showing the primary relaxation time and the breakage time[25].…”
mentioning
confidence: 99%
“…As the structure of this flowing microstructure cannot be deduced solely from interpreting scattering data in the 1-3 plane as demonstrated and noted in this prior literature, additional measurements in the plane of flow (the 1-2 plane) are made to understand the nature of the effects of shear on the local microstructure under flow. This is performed using a recently developed novel sample environment for SANS under flow ; Gurnon et al (2014b); Liberatore et al (2006); Gurnon et al (2014c)]. …”
Section: Introductionmentioning
confidence: 99%